Early stone emplacement in three Scottish ecclesiastical national monuments (Proceedings of the Society of Antiquaries of Scotland, 2009)
The stonework at three well-known Scottish ecclesiastical buildings has been examined in detail. In each, the orientation of the bedding layers in individual stones in certain quoins and arch jambs, and in two instances the wall faces, indicate when these buildings were first erected. In England, the period of construction would have been described as Anglo-Saxon; in this paper the work is referred to as being of 'Patterned' style. On this evidence each building is ascribed to a particularly early origin.